2019
DOI: 10.1111/hdi.12725
|View full text |Cite
|
Sign up to set email alerts
|

A possible link between polyunsaturated fatty acids and uremic toxins from the gut microbiota in hemodialysis patients: A hypothesis

Abstract: Introduction: Indoxyl sulfate (IS) and p‐cresyl sulfate (p‐CS) are albumin‐bound uremic toxins that are difficult to remove by hemodialysis (HD). Human serum albumin (HSA) carries several compounds, including fatty acids that can bind to site II of HSA and represent competing ligands for uremic toxins. The aim of this study was to investigate the association between fatty acids and uremic toxin plasma levels in patients undergoing HD. Methods: Thirty‐three HD patients (51.5% male, 54.9 ± 10.2 years old, 44.63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
(87 reference statements)
0
4
0
3
Order By: Relevance
“…Taking this fact into consideration, Kemp et al demonstrated a negative correlation between p-CS plasma levels and specific polyunsaturated fatty acids (PUFAs) like docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and gamma-linolenic (GLA) in patients with CKD on HD. This result suggests that PUFAs could contribute to reduce uremic toxin plasma levels in patients with CKD undergoing HD [51].…”
Section: Uremic Toxinsmentioning
confidence: 80%
“…Taking this fact into consideration, Kemp et al demonstrated a negative correlation between p-CS plasma levels and specific polyunsaturated fatty acids (PUFAs) like docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and gamma-linolenic (GLA) in patients with CKD on HD. This result suggests that PUFAs could contribute to reduce uremic toxin plasma levels in patients with CKD undergoing HD [51].…”
Section: Uremic Toxinsmentioning
confidence: 80%
“…Além disso, os AGPIs de hemácias do nosso estudo diferem dos resultados anteriores. 48 , 55 , 57 Isto pode ser devido à falta de padronização da análise de AG circulante. Os AG das hemácias são expressos em percentagens do AG total, o que significa que os níveis de AG dependem dos AG analisados pelo método.…”
Section: Discussionunclassified
“…Traditional cardiovascular risk factors do not reflect the full complexity of the atherosclerotic disease, so much so that emerging cardiovascular risk factors have gained emphasis in the literature, 18 , 45 - 48 and the effects of PUFA on CVD are beyond these factors. 18 Among the various non-traditional risk factors, it has been shown that sdLDL-c is a better predictor of CAD risk than LDL-c. 1 The current study found that RBC n-6 PUFA and n-6/n-3 ratio were positively associated with smaller average LDL particle size and higher levels of sdLDL-c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa endotoxemia metabólica leva a um estresse oxidativo, e à produção de lipídios aterogênicos, LDL oxidado (LDLox) e fosfolipídios oxidados – que levam à resposta inflamatória do complexo CD36-TLR4-TLR6. 35 , 36 Ainda, o consumo elevado de AGSs aumenta os níveis de lipídios, de LDL minimamente modificada e de LDLox, que ativam a via inflamatória CD14-TLR4-MD2. 35 O consumo elevado de AGSs também pode alterar a composição lipídica do HDL e a capacidade de efluxo do colesterol, diminuindo sua função e aumentando o risco cardiovascular.…”
Section: Discussionunclassified